2015
DOI: 10.1177/2327857915041035
|View full text |Cite
|
Sign up to set email alerts
|

Supporting dispatch decisions in interfacility medical transfers: Understanding the roles of uncertainty and reliability

Abstract: Efficient transfer of patients between facilities is a key component of regionalized critical care systems, but interfacility transfers pose added risks to patients. We created a decision support tool for dispatchers in medical transportation systems which provides estimates of the time to definitive care, the time between receiving the transfer request and patient handoff, which is a key component of dispatch decisions. This tool provides point-estimates of transfer times that are more accurate than the dispa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Time to definitive care estimates were given to the other decision makers involved in the transfer process (e.g., the TMP) to assist in their medical triage and level of care decisions. Similar to our previous findings (Giang et al, 2015), we found that the planners rarely used the transfer time estimates provided by the CAD software, but instead relied on cues such as the distance, their knowledge of the vehicle speeds, and their own experience in determining the closest or fastest resource. Only in cases that they felt were close did they explicitly calculate the time to definitive care for the 'matching resource to transfer' goal state.…”
Section: Discussion and Futureworksupporting
confidence: 86%
See 1 more Smart Citation
“…Time to definitive care estimates were given to the other decision makers involved in the transfer process (e.g., the TMP) to assist in their medical triage and level of care decisions. Similar to our previous findings (Giang et al, 2015), we found that the planners rarely used the transfer time estimates provided by the CAD software, but instead relied on cues such as the distance, their knowledge of the vehicle speeds, and their own experience in determining the closest or fastest resource. Only in cases that they felt were close did they explicitly calculate the time to definitive care for the 'matching resource to transfer' goal state.…”
Section: Discussion and Futureworksupporting
confidence: 86%
“…A follow-up observational study examined whether Ornge's dispatchers would use information about uncertainty and reliability of the time estimates in a proposed decision support tool. This study revealed that expert dispatchers wanted to see information about the reliability of time estimates in order to judge whether they should revert to alternative estimation methods (Giang, Donmez, Zakir, Ahghari, & MacDonald, 2015). However, the observations also showed that the transport mode decision was only one small aspect of the dispatch task.…”
Section: Introductionmentioning
confidence: 92%
“…Presentation of uncertainty information in addition to point estimates has been shown to enhance operator predictions in other domains, such as weather forecasting (Nadav-Greenberg & Joslyn, 2009). Within the medical dispatch context, observational studies and interviews with Ornge dispatchers have found that expert dispatchers would use information about the variability of time estimates to judge whether they should revert to alternative estimation methods (Giang, Donmez, Zakir, Ahghari, & MacDonald, 2015). Thus, historical transfer time data can be visualized to help users understand both the central tendency and the past variability (i.e., uncertainty) associated with the patient transfer being considered which may result in better patient transfer time estimates.…”
Section: Introductionmentioning
confidence: 99%
“…However, time estimation strategies can vary between different dispatchers, due to elements such as experience and knowledge of the situation (Giang, Donmez, Zakir, Ahghari, & MacDonald, 2015;Giang, Hui, Donmez, Ahghari, & Macdonald, 2016). Thus, it is also possible that individual dispatchers may use a tool meant to support and standardize time estimation in different ways.…”
Section: Introductionmentioning
confidence: 99%